Analisis Kesalahan Siswa dalam Menyelesaikan Soal Konversi Satuan Panjang - Akina; Mufidah; Serlin Tadjila (Universitas Tadulako, 2021)
The purpose of this study was to determine the types of errors in fourth grade students of SDN 4 Tentena in solving length unit conversion problems. This type of research is qualitative research. The subjects of this study were 3 students taken from 13 fourth grade students of SDN 4 Tentena. The results showed that the types of errors made by fourth grade students of SDN 4 Tentena in solving unit length conversion problems seen from the mathematical object were fact errors, conceptual errors, principle errors, and skill/procedural errors. The factors that cause students to make mistakes in solving unit length conversion problems are: students cannot change the problem in story problems into mathematical form, students' skills to solve problems are still lacking, students do not understand the concept of unit length conversion, students have not mastered the use of arithmetic operations, and learning activities carried out at home.